PENDAFTARAN SISWA BARU ONLINE DI SMK NEGERI 4 KENDAL - Haris Ihsanil Huda; Maya Utami Dewi (Elkom : Jurnal Elektronika dan Komputer, 2018)
The development of information systems is increasingly rapidly nowadays requires a lot of educational institutions to develop information systems in educational environments that do not fall behind with other educational institutions. It's possible the parents and students will move to the educational institutions that have information systems that fast, accurate and reliable way to get the information required with skills no doubt in supporting the learning system. SMK Negeri 4 Kendal is located at Jl. Soekarno-Hatta Kendal, very aware of the importance of information systems. The information that fast, accurate and available at all times would be very helpful in the implementation of the learning process is also in the process of admission of new students. A newly established education institution four years ago was very concerned about the availability of information systems needed by students and parents so that information systems and the fabric of cooperation to do with ease. The purpose of this research is to increase the number of new admissions and quality of service in the admission of new students and in conducting the data collection and reporting so that information needed by prospective students as well as guardians and leaders mmurid can be obtained at any time. In this research, the application used is PHP programming MySQL database.